Seed traits inheritance in Fagopyrum esculentum Moench. based on image analysis method - Oh, Min Ah; Park, Ji Eun; Kim, Jae Young; Kang, Ho-Min; Min Oh, San Su; Mansoor, Sheikh; Chung, Yong Suk (Frontiers in Plant Science, 2024)
Common buckwheat (Fagopyrum esculentum Moench.) is one of the most important orphan crops worldwide. Various research efforts have been done to improve cultivation methods to enhance important agronomic traits such as productivity and biotic/abiotic resistance. One important aspect is the seed trait, which has not been extensively studied due to the time-consuming and tedious nature of its examination. Despite this, understanding seed traits is crucial for meeting consumer needs and optimizing crop yields. Therefore, the aim of the study is to investigate the inheritance of common buckwheat seed traits—such as shape, size, and coat color—using an image-based approach. This method allows for the analysis of a large number of seeds with a level of accuracy and precision that was previously unattainable. The results indicate that seed coat color is inherited maternally. Notably, the parameters in size had substantial increases acting like overdominance. The number of seeds that were harvested from F1s of each cross differed a lot depending on the cross combinations and pin/thrum type. In addition, seed size had large reduction in F1s from the different seed-sized parents, especially in thrum type. These may show that there could be cross barriers. The results revealed trends of maternal inheritance for seed shape and coat color in buckwheat, an area that has not been extensively studied. These findings could support buckwheat breeding efforts, helping to address market needs and food demands in the face of significant climate change.